EFEKTIFITAS PEMBERIAN SOSIS TEPUNG TEMPE CAMPURAN JAMUR TIRAM DAN SOSIS TEPUNG AMPAS TAHU CAMPURAN JANTUNG PISANG TERHADAP TINGGI BADAN BALITA STUNTING - Mayang Wulan; Fina Kusuma Wardani; Nuriah Arma (Universitas Prima Indonesia, 2023)
North Sumatra is listed as a province with a high incidence of stunting at 32.4% (concise 13.2% and short 19.2%). The products of tempeh flour sausage mixed with oyster mushrooms and tofu pulp flour sausage mixed with the banana heart present a nutrient-rich food sausage product that is good for consumption by children. The study aimed to determine the effectiveness before and after giving tempeh flour sausage mixed with oyster mushrooms and tofu pulp flour sausage mixed with the banana heart on the increase in the height of stunted toddlers. Type of quantitative research with the pre-experimental method with pretest and posttest control group design. This research is located in Belawan Sicanang Village, Medan Belawan District. Samples in the study were toddlers who were stunted with sampling using the purposive sampling technique. The intervention gave tempeh flour sausage mixed with oyster mushrooms for 60 consecutive days in the first intervention group and sausage flour combined with a banana heart for 60 straight days in the second intervention group and did nothing in the control group. Based on the Paired Samples Test, the oyster mushroom mixed tempeh flour sausage group sig value is 0.000, the banana heart mixed tofu pulp sausage intervention group sig 0.000, and in the control group, the sig value is 0.078. There is an effectiveness of giving tempeh flour sausage mixed with oyster mushrooms on the height of stunted toddlers.